Biological control of eucalyptus bacterial wilt with rhizobacteria - Santiago, Thais R.; Rossato, Mauricio; Romeiro, Reginaldo S.; Mizubuti, Eduardo S. G.; Grabowski, Cristhian (Biological Control, 2015)
The antagonistic potential of 298 rhizobacteria obtained from the rhizosphere and rhizoplane of tomato and eucalyptus plants was assessed for the control of bacterial wilt of eucalyptus caused by Ralstonia solanacearum. Several tests were performed using tomato plants as a screening system to select efficient rhizobacteria. Different methods for antagonist delivery and pathogen inoculation were evaluated: (1) seeds were microbiolized (soaked for 12 h in a suspension of the antagonist propagules) and germinated seedlings had their roots immersed in the pathogen inoculum suspension; (2) seedlings originated from microbiolized seeds were transplanted to soil infested with R. solanacearum and (3) roots of seedlings were immersed in a suspension of propagules of the antagonist and subsequently in a suspension of R. solanacearum. Nine isolates (UFV-11, 32, 40, 56, 62, 101, 170, 229, and 270) were selected as potential antagonists to R. solanacearum as they suppressed bacterial wilt in at least one of the methods assessed. The selected antagonists were evaluated against two isolates of R. solanacearum using in vitro and in vivo (inoculated eucalyptus) tests. Isolates UFV-56 (Bacillus thuringiensis), UFV-62 (Bacillus cereus) and a commercial formulation of several rhizobacteria (Rizolyptus®) suppressed bacterial wilt in eucalyptus protecting the plants during the early stages of development.
Keywords: Ralstonia solanacearum; Biocontrol; Tomato; PGPR